WEAVING AND TYPES OF KNITTED MATERIALS - Gafurov Jahongir Kabulovich; Abdurakhimova Manzura Sadykovna (Western European Studies, 2024)
This article explores various types of weaving techniques used in the production of knitted materials, focusing on the significance of ring counts and their impact on the final products. It provides a comprehensive overview of different weaving methods and their applications in creating diverse knitted fabrics. The study examines how variations in the number of rings influence the properties and quality of these materials and it details the range of products manufactured from them. By analysing the relationship between weaving techniques, ring structures, and product outcomes, the article aims to offer valuable insights into the textile industry's practices and innovations in knitted fabric production
Keywords: material name; light industry; clothing; ring column